ANALISIS KEMAMPUAN LITERASI MATEMATIS SISWA DALAM MENYELESAIKAN MASALAH SISTEM PERTIDAKSAMAAN LINEAR DUA VARIABEL (SPtLDV) DITINJAU DARI GAYA BELAJAR - Harfin Lanya; Istiqomatul Maghfiroh (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2026)
This study aims to describe the level of students' mathematical literacy abilities in terms of visual, auditory, and kinesthetic learning styles in solving problems of two-variable linear inequality systems. The research method used is a qualitative method with a descriptive qualitative approach. Data were obtained using learning style questionnaire instruments, mathematical literacy ability tests, and interviews. The data analysis technique applied in this study uses the Miles and Huberman model. The results of this study indicate that 1) Students who have a visual learning style are able to formulate situations mathematically, are able to use mathematics, and are able to interpret and evaluate mathematics. Students with a visual learning style are also included in the high category for the level of mathematical literacy abilities based on the scoring results. 2) Students who have an auditory learning style are able to formulate situations mathematically, are able to use mathematics, and are able to interpret and evaluate mathematics. Students with an auditory learning style are also included in the high category for the level of mathematical literacy abilities based on the scoring results. 3) Students with a kinesthetic learning style are able to formulate situations mathematically, are able to use mathematical concepts, but are not yet fully able to use mathematical procedures correctly, and are not yet able to interpret and evaluate mathematical results. Students with a kinesthetic learning style are also included in the medium category for the level of mathematical literacy ability based on their scoring results.